Effective Factors on Educational Status of Midwifery Students in Babol University of Medical Sciences - Fatemeh Bakouei; Farzan Kheirkhah; Hajar Salmalian; Shabnam Omidvar (Kerman University of Medical Sciences, 2010)
Background & Objective : Students educational success is of utmost importance As educational slump has always been a great concern in different fields this study was conducted to assess ≤ the effective factors on educational status of midwifery students in Babol University of Medical Sciences Methods: This descriptiveanalytical study was conducted on 152 midwifery students According to the Grade Point Average (GPA) of previous terms students were classified into three groups including good (GPA ≥ 17) average (14